Bioefficacy of organic acids against Colletotrichum gloeosporioides (Penz.) Penz. and Sacc., causal organism of mango (mangifera indica L. cv. "Carabao") anthracnose - Yanos, Rhea M.; Hernandez, Hidelisa P.; Sabularse, Veronica C.; Dalisay, Teresita U. (2021)
"Anthracnose caused by Colletotrichum gloeosporioides (Penz.) Penz. and Sacc. is considered as the most serious and the most important field and postharvest disease of mango fruits. In this study, the bioefficacy of some organic acids against the pathogen isolated from mango is reported. Formic acid, acetic acid, benzoic acid (BA), salicylic acid (SA), p-hydroxybenzoic acid (p-HBA), and m-hydroxybenzoic acid (m-HBA) showed activity gainst C. gloeosporioides" - title page.
Includes bibliographical references.
Keywords: Colletotrichum gloeosporioides -- Philippines; Conidia -- Philippines; Anthracnose -- Philippines; Organic acids